LEVANTAMENTO DE INVERTEBRADOS NO BOSQUE DOS CAPUCHINHOS, IJUÍ – RS - Bianchi, Vidica; Cruz, Taisson K. T. d.; Marques, Roberta; Silva, Anderson F.; Neckel, Jeanine d. M.; Basso, Eloisa G. d. P. (Salão do Conhecimento, 2013)
Resumo